The Protective Effect of Curcumin on the Proliferation and Colonization of Spermatogonial ‎Stem Cells ‎in Gamma-Irradiated Rats - Sareh Azarmi; ‎khosro Hoseini ‎pajooh; Parviz Tajik; ‎Marziyeh Lashkari (Fasa University of Medical Sciences, 2022)
Background & Objective: One of the side effects of radiotherapy can be damage to spermatogonial stem cells that ‎may lead to spermatogenesis disorders and sterility. Protective effects of curcumin on normal cells ‎against radiotherapy side effects have already been shown. In the current study, the protective effects of curcumin ‎on the spermatogonial stem cells against gamma radiation were ‎evaluated.‎ Materials & Methods: This study was done on 50 adult rats in 10 experimental groups. Four groups were ‎injected 0, 25, 50, or 100mg/kg of curcumin in 1ml olive oil for 15 days intraperitoneally, then exposed to radiation ‎at 2 Gy on the next day. Also, four groups were treated like above but without radiation; and two groups as control with and without radiation.  The day after radiation, all of the rats were euthanatized, their testes were removed, and they underwent enzymatic digestion to co-culture spermatogonial stem cells. After 12 days, the colonization of spermatogonial stem cells was assessed. ‎ Results: There was a significant decrease in the colonization of spermatogonial stem cell proliferation ‎in groups that had taken radiation but not curcumin. There was a significant increase ‎ in the colonization of spermatogonial stem cells in the group which had taken radiation whit maximum curcumin compared with the other irradiated groups and ‎was similar to non-irradiated control animals. Colonization of spermatogonial stem cells in non-irradiated animals treated with curcumin had increased compared with control groups.‎ Conclusion: Injection of curcumin can protect spermatogonial stem cells against ‎radiation. Thus, curcumin may prevent sterility in men who undergo radiotherapy. ‎